Choosing Wisely. Issue 3 (May 2016) - Simpson, Kathleen Rice
Abstract : Providing health information at the appropriate literacy level and in enough detail so women are empowered to make wise choices for their care is one of the most important aspects of perinatal nursing. Unnecessary interventions increase risk of patient harm and result in excess healthcare costs. Choosing wisely promotes patient safety and sensible use of limited health resources.